Real-world experience with 0.2 μg/day fluocinolone acetonide intravitreal implant (ILUVIEN) in the United Kingdom - Bailey, C (Eye (Lond), 2017)
AIMS: To compare safety outcomes and visual function data acquired in the real-world setting with FAME study results in eyes treated with 0.2 μg/day fluocinolone acetonide (FAc). METHODS: Fourteen UK clinical sites contributed to pseudoanonymised data collected using the same electronic medical record system. Data pertaining to eyes treated with FAc implant for diabetic macular oedema (DMO) was extracted. Intraocular pressure (IOP)-related adverse events were defined as use of IOP-lowering medication, any rise in IOP>30 mm Hg, or glaucoma surgery. Other measured outcomes included visual acuity, central subfield thickness (CSFT) changes and use of concomitant medications. RESULTS: In total, 345 eyes had a mean follow-up of 428 days. Overall, 13.9% of patients required IOP-lowering drops (included initiation, addition and switching of current drops), 7.2% had IOP elevation >30 mm Hg and 0.3% required glaucoma surgery. In patients with prior steroid exposure and no prior IOP-related event, there were no new IOP-related events. In patients without prior steroid use and without prior IOP-related events, 10.3% of eyes required IOP-lowering medication and 4.3% exhibited IOP >30 mm Hg at some point during follow-up. At 24 months, mean best-recorded visual acuity increased from 51.9 to 57.2 letters and 20.8% achieved ≥15-letter improvement. Mean CSFT reduced from 451.2 to 355.5 μm. CONCLUSIONS: While overall IOP-related emergent events were observed in similar frequency to FAME, no adverse events were seen in the subgroup with prior steroid exposure and no prior IOP events. Efficacy findings confirm that the FAc implant is a useful treatment option for chronic DMO.